2015
DOI: 10.1097/j.pain.0000000000000115
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal resiniferatoxin in a dog model

Abstract: Resiniferatoxin (RTX) is the most potent amongst all known endogenous and synthetic agonists for the transient receptor potential vanilloid 1 (TRPV1) receptor, which is a calcium permeable non-selective cation channel, expressed on the peripheral and central terminals of small diameter sensory neurons. [11,32] Prolonged calcium influx induced by RTX causes cytotoxicity and death of only those sensory neurons that express the TRPV1 ion channel leading to selective targeting and permanent deletion of the TRPV1-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 37 publications
7
84
0
Order By: Relevance
“…postural reactions, except one RTX-treated male that was judged "slightly paralytic" on both the pre-dose day and study day 15, indicating no treatment-related event (Supplemental Table 1). In the client-owned dog study, postinjection increases in heart rate and blood pressure, as reported in prior studies (15,16), were self-limiting and did not require intervention beyond maintenance of general anesthesia until the majority of the autonomic response had subsided. All dogs recovered uneventfully from general anesthesia and were discharged, ambulatory, from the recovery room within 3 hours of extubation.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…postural reactions, except one RTX-treated male that was judged "slightly paralytic" on both the pre-dose day and study day 15, indicating no treatment-related event (Supplemental Table 1). In the client-owned dog study, postinjection increases in heart rate and blood pressure, as reported in prior studies (15,16), were self-limiting and did not require intervention beyond maintenance of general anesthesia until the majority of the autonomic response had subsided. All dogs recovered uneventfully from general anesthesia and were discharged, ambulatory, from the recovery room within 3 hours of extubation.…”
Section: Resultsmentioning
confidence: 52%
“…To further examine the genes that change in any of the data sets, we examined the profiles of these in several other data sets to sive primary afferent neurons for veterinary (14)(15)(16) and human (17) pain conditions. Because TRPV1 is expressed only in specific subpopulations of primary nociceptive afferents in all species in which this has been carefully examined, this approach is thought to spare most normal nonpainful sensations as well as some pain modalities such as pinch or pinprick, which can be transmitted even after deletion of the TRPV1 + afferents in rodents (14).…”
Section: Resultsmentioning
confidence: 99%
“…To test the effectiveness of intrathecal administration of RTX in treating cancer pain, a clinical trial has been initiated by National Institute of Dental and Craniofacial Research (NCT00804154). Usefulness of RTX has been shown in several modalities of pain [24,[26][27][28][29][30][31]. Karai et al [26] reported that intraplantar administration of RTX produced thermal antinociception without affecting basal pain sensitivity.…”
Section: Transient Receptor Potential Vanilloid 1 (Trpv1) Is a Camentioning
confidence: 99%
“…Intrathecal resiniferatoxin, a potent TRPV1 agonist, has been shown to have a potent antihyperalgesic effect in canine persistent pain models [384] and is currently in human clinical trials (http://clinicaltrials.gov/show/NCT00804154). A further modality for targeting TRPV1-bearing neurons takes advantage of the fact that when activated TRPV1 forms a pore that is able to pass large charged molecules.…”
Section: Trpv1 Receptorsmentioning
confidence: 99%
“…Owner-completed questionnaires have been validated to assess the severity and impact of chronic pain syndromes in dogs with bone cancer and osteoarthritis [488]. Such inventories have been shown to be useful in defining the efficacy of a variety of spinal and [261,384] systemic [489] therapies (see [490]. Strengths of such tools include its incorporation of animal behavior over a period of time as opposed to assessment once under the influence of an abnormal environment.…”
Section: Preclinical Assessments In Spinal Analgesic Drug Developmentmentioning
confidence: 99%